El principio de eficiencia en la gestión y sanción de las ordenanzas municipales. - Lucero Lema, Lenin Ronaldo (2025)
The current research addressed the principle of efficiency in management and enforcement of municipal ordinances to determine whether the Municipal Council of the Decentralized Autonomous Government of the Riobamba Canton complies with the deadlines established by law for the creation of municipal ordinances. Currently, the Decentralized Autonomous Government of the Riobamba Canton has created several ordinances to legalize urban land; however, these have been delayed unjustifiably for several years, preventing citizens from legalizing their properties and violating constitutional rights such as property and housing. This has led to the establishment of unnecessary bureaucracy, resulting in slow processing of deeds. This research was conducted using the analytical legal method, descriptive legal method, and correlational legal method, with a non-experimental design, legal dogmatics, and a qualitative approach. Surveys were applied to municipal employees, administrators, or the beneficiary population of the management and enforcement of ordinances related to land legalization, as well as to lawyers in private practice with expertise in Administrative Law. This methodology allowed me to achieve the outlined objectives. In conclusion, it can be determined that the 90-day deadline for publishing municipal ordinances, as stipulated in Article 324 of the COOTAD, is not being met, thereby violating an administrative principle—efficiency—set forth in Article 4 of the Organic Administrative Code (COA) in the management and enforcement of municipal ordinances.